KNOWLEDGE OF CLEAN AND HEALTHY LIFE BEHAVIOR WITH TRACOMA PREVENTION MEASURES IN THE ELDERLY - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Setyo Bagus Hariyanto (UPT Penerbitan Universitas Jember, 2023)
Background: The problem of a person's lack of knowledge about eye diseases can cause a lack of understanding in the community. Elderly who live with their families do not know how to live a clean and healthy life. Implementation of clean and healthy living behavior in the household order by the community is still below standard. The aims to analyze knowledge of clean and healthy living behavior with trachoma disease prevention measures in the elderly. Methods: The research design used cross-sectional, namely measuring knowledge of clean and healthy living behavior towards prevention of trachoma in the elderly. Sample research, namely elderly who are still healthy who are in the working area of ​​the Patrang Public Health Center as many as 52 respondents. Through a purposive sampling technique with inclusion criteria including: 1) elderly aged 50-85 years and carried out screening using the MMSE questionnaire; 2) can communicate well and smoothly; 3) cooperative elderly; 4) willing to be a respondent. Researchs data obtained from the results of filling out questionnaires by respondents. Then the data is tested for analysis Rank Spearman’s correlation using the SPSS statistic with a p value <0.05. Results: The research results show the knowledge of clean and healthy living behavior is mostly in the sufficient category as many as 26 respondents (50%). Trachoma disease prevention measures in the elderly are mostly in the good category as many as 33respondents (63%). There is a relationship between knowledge of clean and healthy living behavior and prevention of trachoma in the elderly, with a p = value 0.001, and value r = 0.543 means that it has a positive or unidirectional relationship with moderate correlation strength. Conclusions: Knowledges of clean and healthy living behavior can shape a person's actions or behavior for the better. Knowledge of clean and healthy living behavior can be learned and or can be obtained through information from various sources and methods (print or electronic form). So that can take preventive measures against trachoma in the elderly.